Distribution of the CPU time of a reservoir simulator - Awang, Mariyamni (Faculty of Chemical & Natural Resources Engineering, 1991)
The aims of this investigation was to obtain the time consuming computations in a reservoir simulator. A fully implicit oil-gas model was tested. The Newton-Raphson technique and the Gaussian elimination method were used in the simulation. To reduce the overall CPU time, the results showed that small simulators need efficient table look-up methods, while large simulators need efficient matrix solvers.